An economic assessment on public well-being for biodiversity conservation in Gunung Mulu National Park, Sarawak, Malaysia - Johari, Shazali; Adam Assim, Mohamad Ibrani Shahrimin; Wan Mohammad, Syarifah Kamariah; Mohammad Afandi, Syamsul Herman (2024)
The economic valuation is crucial to estimate non-marketed goods, which refer to public willingness to pay (WTP) for conservation efforts in the tourism area. Both local communities and visitors play an important role in developing sustainable tourism and well-being. However, the information on economic valuation based on their preferences and well-being is still limited in the world heritage site Gunung Mulu National Park (GMNP). Thus, the study attempts to elucidate the WTP on how the local community and visitors value biodiversity conservation in GMNP through park entrance fees and how it relates to conservation awareness and community well-being in the area. The validated questionnaire was distributed to the visitors (n = 87) and the local community (n = 99) through an online and face-to-face approach, respectively. From the study, the estimated mean WTP among the public was MYR40.61 (USD9.60) per entry, which is highly influenced by their level of attitude and experience. The level of attitude among the respondents has influenced the WTP for the existing park entrance fee. Meanwhile, there is no awareness construct that affects the WTP for increased fees among visitors and the local community. The low level of knowledge and experience of the respondents but the high level of attitude has influenced the good WTP for the cheaper park entrance fee. It is noted that certain socio-demographic factors had influenced their WTP for the offered and maximum price. It was found that the environment and social factors have significantly influenced the WTP among the public. However, the economic factor did not predict their WTP. The findings enhance the relationship between crucial social value determinants and the economy, particularly on WTP in a protected area.